Triclosan has a strong influence on the development of mouse preimplantation embryo via activating miR-134/Nanog axis. (November 2022) - Yang, Ye; Ni, Danyu; Wang, Li; Shi, Xiaodan; Zhang, Xiaolan; Zhou, Lin; Ji, Juan; Zhao, Chun; Shen, Rong; Ling, Xiufeng; Chen, Xiaojiao
Abstract: Antimicrobial triclosan (TCS), one of the popular ingredients added to sanitizing products, has widespread use in personal care. However, it poses potential risks to reproduction and development. Unfortunately, the underlying mechanisms remain largely unclear. This study aimed to investigate effects of TCS on the development of preimplantation mouse embryo and explore related mechanisms Mouse zygotes were collected and cultured to blastocysts in KSOM medium supplemented with four different concentrations of TCS. The development rates, pluripotency or stem cells markers, and microRNA (miR)− 134 were compared between control and experimental groups across each specific developmental stage. Prolonged exposure to TCS remarkably impaired early embryo development in vitro by hampering morula and blastocyst formations (P < 0.05, P < 0.001). The arrest of embryo development was linked with decreased expressions of pluripotency or stem cells markers, especially Nanog and Notch1. Moreover, based on miRWalk database and in vitro luciferase assays, we confirmed that miR-134 induced by TCS was a negative regulator of Nanog. Crucially, impaired TCS-treated embryos could be rescued by inhibiting miR-134 or forced overexpressing Nanog mRNA. Altogether, our results highlight that pathologically relevant level of TCS compromises preimplantation mouse embryo development by inducing miR-134 and triggering miR-134/Nanog axis. Considering high conservative of miR-134 between human and mouse, it should be the most promising potential target to regulate development of preimplantation embryo.